PHRASEOLOGICAL «HIGHLIGHTS» OF THE SUBDIALECT OF THE TIUDIV OF KOSIV DISTRICT - Голянич, М. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article lexicographically studies the phraseological units, manifesting the subdialect of the village of Tiudiv of Kosiv District of Ivano-Frankivsk Region. Of the research there come out the peculiarities of the Hutsul dialect.